(untitled) (Research, Society and Development, 2023)
Objective: To analyze the decontamination by thermodisinfection of reused N95 masks. Methodology: Experimental study, with 10 N95 masks reused for 12 hours with a 60-hour rest period, for a total of 60 hours of reuse (following the orientation of the Health Agencies, the prolonged use did not exceed 8 hours, nor reuse for 120 hours) in a hospital in an area that generates aerosols. The reused masks were sown touching the inner part closest to the nose and mouth in a Chocolate Agar culture medium, and then submitted to decontamination by a thermo-disinfector at a temperature of 90°C for 1 hour. The plates were incubated in the biological oven at 36°C for 48 hours. After seeding, macroscopic characterization of the colonies and Gram staining was performed. Results: After the decontamination process, there was no development of microorganisms, when compared to the amount of colonies before decontamination where 2 to 14 colonies ranging from gram+ cocci to gram- Bacillus were detected. Conclusion: After thermal disinfection of N95 masks, there was an absence of microorganisms at the decontamination level; however, the masks were damaged and could not be reused. It is important to develop new studies that allow both the decontamination of N95 masks and their reuse while maintaining the filter barrier.